ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN MATEMATIKA DI SMP NEGERI 22 SAMARINDA - Fauziah, Sahdina; Dimpudus, Ariantje (Universitas Bhinneka PGRI, 2025)
The purpose of this study was to analyze the implementation of the Merdeka curriculum in the planning and learning process in mathematics subjects based on the Merdeka curriculum platform Circular Letter of the Ministry of Education, Research, and Technology Number 2093/B.B1 concerning the Notification of the Merdeka Teaching Platform for Teachers and Education Personnel in 2023 at SMP Negeri 22 Samarinda. The subjects of this study were mathematics teachers at SMP Negeri 22 Samarinda and the objects of this study were the planning and implementation of learning in mathematics subjects. Data were collected through interviews, observations, and documentation, then analyzed by reducing data, presenting data, and drawing conclusions. The results of the data analysis showed that the learning planning containing learning outcomes (CP), Learning Objectives (TP), Learning Objective Flow (ATP), teaching modules, and Learning Objective Achievement Criteria (KKTP) were in accordance with the direction of the Ministry of Education, Culture, Research, and Technology. However, in terms of learning implementation, there was a discrepancy between what was written in the planning (teaching module) and its implementation, especially in the interactive, inspiring, fun, motivating components, and providing sufficient space for students.